2014
DOI: 10.1016/j.meegid.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito and sand fly gregarines of the genus Ascogregarina and Psychodiella (Apicomplexa: Eugregarinorida, Aseptatorina) – Overview of their taxonomy, life cycle, host specificity and pathogenicity

Abstract: Mosquitoes and sand flies are important blood-sucking vectors of human diseases such as malaria or leishmaniasis. Nevertheless, these insects also carry their own parasites, such as gregarines; these monoxenous pathogens are found exclusively in invertebrates, and some of them have been considered useful in biological control. Mosquito and sand fly gregarines originally belonging to a single genus Ascogregarina were recently divided into two genera, Ascogregarina comprising parasites of mosquitoes, bat flies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 87 publications
1
29
0
2
Order By: Relevance
“…However, the presence of parasites in the seminal vesicles of insects has not been observed so far, therefore this is the first study that provides the record of gregarine apicomplexan parasites in this reproductive organ. The infection process by gregarine in seminal vesicles of T. castaneum probably occurs with a similar mechanism as described by Lantova and Volf 10 for the accessory glands of the female of sand flies. In this study it was reported that the gregarines enter into the intestinal cavity through ingestion, go through the intestinal wall and reach the accessory gland, where they adhere to the wall and finally are released into the gland lumen.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…However, the presence of parasites in the seminal vesicles of insects has not been observed so far, therefore this is the first study that provides the record of gregarine apicomplexan parasites in this reproductive organ. The infection process by gregarine in seminal vesicles of T. castaneum probably occurs with a similar mechanism as described by Lantova and Volf 10 for the accessory glands of the female of sand flies. In this study it was reported that the gregarines enter into the intestinal cavity through ingestion, go through the intestinal wall and reach the accessory gland, where they adhere to the wall and finally are released into the gland lumen.…”
Section: Discussionsupporting
confidence: 59%
“…In this study it was reported that the gregarines enter into the intestinal cavity through ingestion, go through the intestinal wall and reach the accessory gland, where they adhere to the wall and finally are released into the gland lumen. The occurrence of intestinal gregarine has already been recorded for several insects, including the tenebrionid beetles 4, 19 , and the contamination process is known, which occurs through ingestion of oocysts during feeding 10, 20 . In the earthworm seminal vesicles the life cycle and infection process were well established and showed that the contamination occurred by an oro-fecal route, with the parasite crossing the intestinal wall to reach the dorsal vessel and the heart from where it was transported to the seminal vesicles 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations